The wild boar and the farmers: the importance of the human dimension in resolving a case of conflict - Fontora, Vitória Margarida Ribeiro (2021)
The high population numbers of wild boar (Sus scrofa) have led to the emergence of several cases of conflict with humans around the world. Thus, in order to seek a solution to the problem, several population management measures have emerged and been applied: hunting, fencing, application of toxins, trapping, supplementary feeding, vaccination, and contraception. However, none of them is fully effective and capable of ending the problem. Thus, ethnobiology and local ecological knowledge (LEK) were used as a tool to help create realistic and achievable wild boar management plans. To this end, 41 semi-structured interviews were conducted with farmers from a village in Viseu, in order to collect their LEK and their attitudes towards wild boar management and conservation plans. It was found that there is an information gap on topics such as the existence of predators, the operation of wild boar hunting and its conservation status. As for conservation attitudes, the vast majority see the wild boar as a problem and a source of expense, opposing its conservation and supporting its extermination. With all this in mind, a multidisciplinary and flexible plan was proposed, with the ability to mold itself to the different needs of different stakeholders in different locations. In parallel, the creation of local organizations responsible for supporting the population affected by the conflict was also proposed. In order to combat misinformation, all of this must be accompanied by a strengthening in the education and awareness of the local population.